The Effect of Implementing SBAR Handover on the Continuity of Nursing Care in Inpatient Wards - Otrina Otrina; Harif Fadhillah; Eni Widiastuti; Muhammad Hadi; Awaliyah Ulfah Ayudytha Ezdha (Indonesian Journal of Global Health Research, 2026)
Continuity of nursing care is an important indicator of hospital service quality and is strongly influenced by the effectiveness of communication among nurses, particularly during handover. One communication method recommended to enhance patient safety is SBAR (Situation, Background, Assessment, Recommendation). Integrating the SBAR method with Jean Watson's caring theory is expected to strengthen clinical communication in a more humanistic and holistic manner. This study aimed to analyze the effect of SBAR handover implementation on the continuity of nursing care in the inpatient wards of Pekanbaru Medical Center Hospital. This study employed a quasi-experimental design with control and experimental groups.This study used a total sampling technique involving 30 inpatient nurses, who were divided into an experimental group (n = 15) and a control group (n = 15). Data were collected by measuring continuity of nursing care scores before and after the intervention. Data analysis was conducted using the Generalized Linear Model Repeated Measures to assess changes in scores over time and differences between groups. The results showed that before the intervention, the mean continuity of nursing care scores were 37.27 ± 5.92 in the control group and 35.67 ± 4.37 in the experimental group. Following the implementation of SBAR handover, scores increased in both groups; however, the improvement was greater in the experimental group, with a mean score of 50.93 ± 1.10 compared to 41.80 ± 3.45 in the control group. The control group showed a statistically significant improvement (p = 0.020), whereas the experimental group demonstrated a highly significant increase (p = 0.000). Between-group analysis revealed a significant difference (F = 9.414; p = 0.005), as well as significant time effects and time × group interaction effects (p = 0.000). In conclusion, the implementation of SBAR handover was effective in improving the continuity of nursing care in inpatient wards.